AKTIVITAS ANTIHIPERTRIGLISERIDEMIA EKSTRAK KUNYIT (Curcuma longa L.) DAN BANGLE (Zingiber cassumunar Roxb.) SERTA KOMBINASINYA PADA HEWAN HIPERTRIGLISERIDEMIA - Patonah Hasbalah (Universitas Bhakti Kencana, 2014)
Background and purpose: Hypertriglyceridemic is a risk factor for cardiovascular disease. Hypertriglyceridemia occurs due to increased levels of triglycerides can lead to accumulation of lipids in the walls of arteries that can lead to atherosclerosis. This research aimsed to study the activity as antihipertrigliseridemia of Curcuma longa extract, Zingiber cassumunar extract and its combination using lipid tolerance test method.Methods: Twenty-eight male Wistar rats were divided into 7 groups randomly. Group 1 (vehicle of drug suspension), group 2 (gemfibrozil (HypofilÂ®) 27 mg / kg bw), group 3 (vehicle of drug suspension), group 4 (Curcuma longa extract 100 mg / kg bw), group 5 (Curcuma longa extract 100 mg / kg bb), group 6 (Curcuma longa and Zingiber cassumunar extracts 50: 50 mg / kg bw), group 7 (Curcuma longa and Zingiber cassumunar extracts 100: 100 mg / kg bw). All groups except group 1 received propylthiouracil (10 mg / kg bw) orally for 5 day. On day 5, two hours after the last administration of drug and PTU, animals were induced by lipid emulsion intravenously. Triglyceride serum levels were measured at 0, 10, 20, 30, 40 minutes. Results: Results showed that Curcuma longa extract, Zingiber cassumunar extract, and its combination, and gemfibrozil (HypofilÂ®) decreased triglycerides levels for 40 minute (p <0, 05) when compared to positive group (induction). The percentage of decrease in triglyceride levels in the 40 minute were gemfibrozil (65.01%), Curcuma longa extract (60.21%), Zingiber cassumunar extract (61.19%), a combination 1 (57.1%), and combination 2 (64.97 %). Conclusion: From this study it can be concluded that Curcuma longa extract, Zingiber cassumunarextract and its combination had antihipertrigliceridemic activity.